ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PURCHASE DECISION PELANGGAN PADA E-COMMERCE TOKOPEDIA - Fadhilah, Rasyad Hafizh; Sfenrianto, Sfenrianto (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
This study aims to determine what factors can influence a customer's purchase decision in e-commerce Tokopedia. There are 5 variables analyzed, namely user experience, consumer behavior, brand awareness, brand image, and trust. In the study, questionnaires were distributed to 400 respondents who had previously transacted using the Tokopedia mobile application and were domiciled in West Java. The questionnaire was administered online using a random sampling technique. The data from the questionnaire will then be analyzed using the SEM-PLS method and the data will be processed by SmartPLS. In this study, there are 5 hypotheses given. Of the 5 hypotheses, 4 are accepted and 1 is rejected. The results of the study stated that the user experience, brand awareness, brand image, and trust variables had a positive and significant effect on a customer's purchase decision at Tokopedia. Meanwhile, the consumer behavior variable has a positive but not significant effect on a customer's purchase decision at Tokopedia. The results of this study are expected to be used as input for Tokopedia to pay more attention to aspects of user experience, brand awareness, brand image, and trust as an effort to improve and maintain customer purchase decisions at Tokopedia. Then this research is also expected to be a learning material for research that dwells in the field of e-commerce and digital business in the future.